Production of the Extremolyte Cyclic 2,3-Diphosphoglycerate Using Thermus thermophilus as a Whole-Cell Factory - De Rose, Simone A.; Finnigan, William; Harmer, Nicholas J.; Littlechild, Jennifer A.; The HotSolute consortium,; Bettina, Seibers; Christopher, Bräsen; Christina, Stracke; Benjamin, Meyer; Misha N., Isupov; Nicholas J., Harmer; Simone, Antonio De Rose; et al. (Frontiers in Catalysis, 2021)
Osmolytes protect microbial cells against temperature, osmolarity and other stresses. The osmolyte cyclic 2,3-diphosphoglycerate, originally isolated from the thermophilic archaeon Methanothermus fervidus, naturally protects cellular proteins under extreme conditions. The biosynthetic pathway for cyclic 2,3-diphosphoglycerate has been introduced into the thermophilic bacterium Thermus thermophilus. The two enzymes in this synthetic pathway, 2-phosphoglycerate kinase and cyclic diphosphoglycerate synthetase, were incorporated into a newly designed modular BioBricks vector. The expression of this two-enzyme cascade resulted in the whole cell production of cyclic 2,3 diphosphoglycerate. In vivo production of cyclic 2,3-diphosphoglycerate was confirmed by mass spectrometry to a concentration up to 650 µM. This study demonstrates the feasibility of using this well studied thermophilic bacterium as a host in a whole-cell factory approach to produce cyclic 2,3 diphosphoglycerate. This raises the potential for commercialisation of cDPG for cosmetic and healthcare applications. Our work demonstrates the potential of Thermus thermophilus as an alternative host for other high value small organic molecules of industrial interest.